Clostridium innocuum is a significant vancomycin-resistant pathogen for extraintestinal clostridial infection. (August 2017) - Chia, J.-H.; Feng, Y.; Su, L.-H.; Wu, T.-L.; Chen, C.-L.; Liang, Y.-H.; Chiu, C.-H.
Abstract: Objectives: Extra-intestinal clostridial infection (EICI) is rare but can be fatal. Traditional phenotypic methods can only assign many of the Clostridium species to the genus level. Methods: A total of 376 non-repetitive Clostridium isolates from sterile sites were collected and subjected to matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) Biotyper analysis and 16S rRNA sequencing. Antimicrobial susceptibility was determined, and clinical characteristics of the patients were assessed. Clostridium innocuum isolates were characterized by genome sequencing and genotyping. We used molecular and cellular methods to explore the virulence and resistance mechanisms of C.   innocuum . Results: Clostridium innocuum was the second most common species to cause EICI, only next to Clostridium perfringens . All Clostridium isolates showed susceptibility to clindamycin, metronidazole, penicillin, piperacillin and ampicillin-sulbatam, while C. innocuum isolates were invariably resistant to vancomycin. Among 24 patients with EICI caused by C. innocuum, two (8.3%) had diarrhoea, three (12.5%) had soft-tissue infection, six (25%) had appendicitis and four (16.7%) each had shock and gastrointestinal perforation. The 30-day mortality was 16.7%. The C. innocuum isolated from different sites could not be separated from one another by genotyping. No known toxin genes were identified in the genome of C. innocuum but the species expressed cytotoxicity to epithelial cells.d -Alanine-d -alanine ligase, alanine racemase andd -alanyl-d -alanine carboxypeptidase are three main genes responsible for vancomycin resistance in C. innocuum . Conclusions: Vancomycin-resistant C. innocuum is a previously unrecognized, yet prominent, cause for EICI. Genome analysis showed that the species could carry a lipopolysaccharide-like structure that is associated with cytotoxicity to cells in vitro .